Transoesophageal Ultrasound Assessment of Lung Aeration in Patients With Acute Respiratory Distress Syndrome - Brault, Clément; Zerbib, Yoann; Kontar, Loay; Maizel, Julien; Slama, Michel (Frontiers in Physiology, 2021)
Introduction: The effect of positive end-expiratory pressure (PEEP) depends closely on the lung’s recruitable/consolidated status. Bedside assessment of lung recruitability is difficult in clinical practice. Methods: We developed a transoesophageal lung ultrasound (TE-LUS) method in which a quantitative (computer-assisted) grayscale determination served as a guide to PEEP-induced lung recruitment. The method is based on the following hypothesis: when the PEEP increases, inflation of the recruited alveoli leads to dramatic changes in the air/water ratio. Normally ventilated areas are hypoechoic because the ultrasound waves are weakly reflected while poorly aerated areas or non-aerated areas are hyperechoic. We calculated the TE-LUS re-aeration score (RAS) as the ratio of the mean grey scale level at high PEEP to that value at low PEEP for the lower and upper lobes. A RAS <1 indicated an increase in ventilated area. We used this new method to detect changes in ventilation in patients with a low (<0.5) vs. high (≥0.5) recruitment-to-inflation (R/I) ratio. Results: We included 30 patients with moderate-to-severe ARDS. In patients with a high R/I ratio, the TE-LUS RAS was significantly lower in the lower lobes than in the upper lobes (0.83 [0.61-0.89] vs. 0.95 [0.73-1.13]; p=0.05). Likewise, the TE-LUS RAS in the lower lobes was significantly lower in the high R/I group than in the low R/I group (0.83 [0.61-0.89] vs. [0.84-1.00]; p=0.03). Conclusion: The increase in PEEP induces a substantial gain in the ventilation of poorly or non-aerated lower lobes (dependent lung regions), especially in patients with a high R/I ratio.